Analisis Kinerja Keuangan Pada PT. Bentoel Internasional Investama Tbk - Rizkia Hikmah; Sihabudin Sihabudin; Robby Fauji Fauji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
PT Bentoel Internasional Investama Tbk. is one of the largest cigarette companies in Indonesia. The cigarette manufacturing sector has a significant contribution to state revenue through excise, as regulated in Law number 39 of 2007. Indonesia ranks the third largest number of smokers in the world with 112 million smokers in 2021. Cigarette companies face intense competition, which forces them to continuously improve product quality and business strategies to maintain market share and maximize profits. This study aims to analyze the financial performance of PT Bentoel Internasional Investama Tbk. This research method uses Kuanitatif with secondary data sources, the research population in the 6-year period 2017-2022 in the financial statements, the sample used financial statements consisting of the balance sheet and profit and loss of PT Bentoel Internasional Investama Tbk 2017-2022, with analysis methods using statistical analysis. The results of the study on the analysis of liquidity ratios using a current ratio of 1.94 rounded 2 is declared good and a cash ratio of 0.10 is declared not good, solvency ratio with a debt to asset ratio of 41% is declared good, the ratio of debt to equity obtained a value of 70% is declared not good, and long-term debt to equity is good 17% is declared good. The activity ratio using the calculation of fixed asset turnover of 2.83 is not good and total asset turnover of 1.15 is not good. The profitability ratio using net profit margin obtained 0% is not good, return of incesment 0% is not good, and return of equity -0.03% is not good.